2003
DOI: 10.1046/j.1365-2958.2003.03668.x
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella SpiC protein targets the mammalian Hook3 protein function to alter cellular trafficking

Abstract: SummaryThe Salmonella SpiC protein is secreted into the cytosol of macrophages via a unique type III secretion system that functions intracellularly to translocate proteins across the phagosomal membrane. The SpiC protein is required for survival within macrophages and inhibition of phagosome-lysosome fusion in vivo , and it is sufficient to inhibit endosome-endosome fusion in vitro . Here, we establish that SpiC targets the function of Hook3, a mammalian protein implicated in cellular trafficking. Purified GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…The only T3SS2 effector that has been implicated in early SCV biogenesis is SpiC/SsaB, a protein that was shown to inhibit membrane fusion [37,38]. But other data suggests that SpiC is a component of the T3SS2 translocon rather than an effector [39] and this issue remains unresolved.…”
Section: T3ss2 Effectors Mediate Intermediate and Late Scv Biogenesismentioning
confidence: 99%
“…The only T3SS2 effector that has been implicated in early SCV biogenesis is SpiC/SsaB, a protein that was shown to inhibit membrane fusion [37,38]. But other data suggests that SpiC is a component of the T3SS2 translocon rather than an effector [39] and this issue remains unresolved.…”
Section: T3ss2 Effectors Mediate Intermediate and Late Scv Biogenesismentioning
confidence: 99%
“…Initially, it was shown to be exported into host cells through T3SS2 and was proposed to interfere with intracellular trafficking to inhibit fusion of SCV with lysosomes [290]. Two host targets have been proposed for SpiC: TassC [291] and Hook3 [292]. TassC is also known as Nipsnap4 or Nps4.…”
Section: Sope and Sope2mentioning
confidence: 99%
“…The SpiC protein is necessary for inhibiting the fusion of Salmonella-containing phagosomes with endosomal and lysosomal compartments (Uchiya et al, 1999). Moreover, this protein is translocated by the SPI-2 TTSS to the cytosol of macrophages, where it interacts with host proteins such as TassC (Lee et al, 2002) and Hook3 (Shotland et al, 2003) to alter intracellular trafficking. On the other hand, several investigators have reported that SpiC is required for the translocation of SPI-2 effector proteins into target cells by interacting with SsaM, a SPI-2-encoded protein (Freeman et al, 2002;Yu et al, 2002Yu et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%